Terminalia arjuna, a Cardioprotective Herbal Medicine-Relevancy in the Modern Era of Pharmaceuticals and Green Nanomedicine-A Review - Purnimajayasree Ramesh; Arunkumar Palaniappan (MDPI AG, 2023)
Herbal medicines were the main source of therapeutic agents in the ancestral era. Terminalia arjuna (TA) is one such medicinal plant widely known for its several medicinal properties, especially its cardiovascular properties. They have several phytochemicals, such as flavonoids, polyphenols, triterpenoids, tannins, glycosides, and several minerals, proteins, and others that are responsible for the above-mentioned medicinal properties. In this review, we have first elaborated on the various processes and their parameters for the efficient extraction of relevant phytochemicals from TA extracts. Secondly, the mechanisms behind the various medicinal properties of TA extracts are explained. We have also highlighted the role of TA extracts on the green synthesis of metallic nanoparticles, especially silver and gold nanoparticles, with an elucidation on the mechanisms behind the synthesis of nanoparticles. Finally, TA extracts-based polymeric formulations are discussed with limitations and future perspectives. We believe that this review could help researchers understand the importance of a well-known cardioprotective medicinal plant, TA, and its biomedical properties, as well as their role in green nanotechnology and various formulations explored for encapsulating them. This review will help researchers design better and greener nanomedicines as well as better formulations to improve the stability and bioavailability of TA extracts.